Analisis konstruksi sintaksis pada slogan kuliner - Fauziyah, Nurul; Aprila, Nanda Riska Dwi (Fakultas Sastra Universitas Negeri Malang, 2022)
This study describes forms of syntactic constructions or syntactic tools on several culinary slogans. This research uses a qualitative descriptive approach, because it describes the forms of syntactic construction categories on culinary slogans on social media or print media and analyzes syntactic constructions on the culinary slogan. The data in this study is based on written data sources in the form of phrases, clauses, sentences, and discourses from culinary slogans that have been collected. This study uses documentation techniques, namely by listening, recording, and classifying the forms of syntactic construction found in culinary slogans to collect data. The analytical technique in this study uses a basic distributional technique, namely the Segmenting Immediate Constituents Technique (Segmenting Immediate Constituens Techniques) which is used to categorize a construction of the direct elements that make up the construction and the orthographic match method or written language because based on the determinants, part of the language studied is in the form of written language, namely culinary slogans.